Whole rock and spinel compositions of serpentinized peridotites from the Divriği-Sivas region, eastern Turkey: Implications for their tectonic setting. (November 2017) - Ünlü, Taner; Akıska, Sinan; Varol, Ece; Öztürk, Ceyda; Mutlu, Halim
Abstract: In this study we investigate the spinel and whole rock chemistry of ultramafic rocks in the Divriği-Sivas region hosting one of the largest ophiolite suites in Turkey, which were emplaced following the convergence between the African and Eurasian plates in the Late Cretaceous. The ophiolitic mélange (Güneş Ophiolite) in Divriği is composed of ultramafic rocks, amphibolites, sub-ophiolitic metamorphic rocks and calc-silicates. The ultramafic rock section is made up of serpentinized wehrlites overlain by irregular segregations of pyroxenite levels. Whole rock chemistry of Divriği wehrlites resembles serpentinized peridotites in Himalayas. They have high MgO (average 31.27 wt%) and low Al2 O3 (average 0.56 wt%) concentrations and Mg/Si and Al/Si ratios imply that peridotites formed in a supra-subduction zone environment. The U-shaped REE patterns of serpentinized wehrlites are formed by partial melting, coupled with interaction between peridotite and hydrous melts in the mantle wedge. The spinels collected from serpentinized wehrlites show compositions ranging from chromite in the core to ferritchromite and Cr-magnetite at the rims and have high Cr2 O3 (46.5–56.2 wt%) and very low TiO2 contents (<0.3 wt%). Cr# values (0.71–0.84) of studied spinels are consistent with those of selected spinels from Anatolian peridotites but their Mg# values (0.26–0.46) are significantly lower. Cr# values of Divriği spinels correspond to SSZ peridotites and indicate high-degree partial melting (>%35). Parental melt compositions computed (8.69–11.71 wt% for Al2 O3 and 0.1 to 0.37 wt% for TiO2 ) from chromite-melt equilibrium conditions yield a boninitic affinity. Our data suggest that spinels from serpentinized wehrlites in the Divriği area are similar to peridotite xenoliths from the Kamchatka arc and West Bismarck. Highlights: Spinel chemistry of ultramafic rocks in the Divriği-Sivas ophiolite has been studied. Chromite composition changes to ferritchromite or Cr-magnetite from core to rim. High-Cr content of spinels yields a boninite type magma formed in SSZ environment. Cr# values of Divriği spinels indicate high-degree partial melting (>%35).